Enhanced climate change response of wintertime North Atlantic circulation, cyclonic activity and precipitation in a 25 km-resolution global atmospheric model - Baker, Alexander J.; Schiemann, Reinhard; Hodges, Kevin I.; Demory, Marie-Estelle; Mizielinski, Matthew S.; Roberts, Malcolm J.; Shaffrey, Len C.; Strachan, Jane; Vidale, Pier Luigi (Journal of Climate, 2019)
Wintertime mid-latitude cyclone activity and precipitation are projected to increase across northern Europe and decrease over southern Europe, particularly over the western Mediterranean. Greater confidence in these regional projections may be established by their replication in state-of-the-art, high-resolution global climate models that resolve synoptic-scale dynamics. We evaluated the representation of the wintertime eddy-driven and subtropical jet streams, extratropical cyclone activity and precipitation across the North Atlantic and Europe under historical (1985-2011) and RCP8.5 sea surface temperature forcing in an ensemble of atmosphere-only HadGEM3-GA3.0 simulations, where horizontal atmospheric resolution is increased from 135 to 25 km. Under RCP8.5, increased (decreased) frequency of northern (southern) eddy-driven jet occurrences and a basin-wide poleward shift in the upper-level westerly flow are simulated. Increasing atmospheric resolution significantly enhances these climate change responses. At 25 km resolution, these enhanced changes in large-scale circulation amplify increases (decreases) in extratropical cyclone track density and mean intensity across the northern (southern) Euro-Atlantic region under RCP8.5. These synoptic changes with resolution impact the overall climate change response of mean and heavy winter precipitation: wetter (drier) conditions in northern (southern) Europe are also amplified at 25 km resolution. For example, the reduction in heavy precipitation simulated over the Iberian Peninsula under RCP8.5 is ∼15% at 135 km, but ∼30% at 25 km resolution. Conversely, a shift to more frequent high ETC-associated precipitation rates is simulated over Scandinavia under RCP8.5, which is enhanced at 25 km. This study provides evidence that global atmospheric resolution may be a crucial consideration in European winter climate change projections.